The Role of Knowledge Management in Enhancing Digital Capability and Driving Innovation in SMEs - Yutika, Fitri (Universitas Muhammadiyah Surakarta, 2024)
The adaptability of SMEs to new technologies is essential for their success in an increasingly competitive market environment. Leveraging digital technology to improve business performance requires strong digital capabilities. Effective knowledge management allows SMEs to enhance their digital capabilities, which not only boosts operational efficiency but also fosters market-relevant innovation. This study explores the role of Knowledge Management in fostering Digital Capability and promoting Digital Innovation among Small and Medium-sized Enterprises in West Kalimantan. Using Structural Equation Modeling, data were collected from 102 SMEs through questionnaires. The findings reveal that Knowledge Management significantly influences Digital Capability and Digital Innovation, with path coefficients of 0.932 and 0.949 and t-statistics of 88.110 and 165.798, respectively. This demonstrates that effective knowledge management can markedly enhance digital capabilities and innovation in SMEs, thereby improving their performance. The study offers valuable insights for policymakers and business leaders. By demonstrating the critical role of Knowledge Management in driving digital transformation, the research provides actionable recommendations for SMEs to invest in Knowledge Management Systems and practices, thereby improving operational efficiency, competitiveness, and adaptability to market changes.